Pencegahan Patologi Birokrasi Melalui Reformasi Adminitrasi Pelayanan Publik - Bernika Bahrum; Evi Priyanti (Peneliti.net, 2022)
The Community Health Center (PUSKESMAS) as the spearhead of the national health service system, is currently almost powerless. The main problem of the Curug Community Health Center in Karawang Regency is the quality of service, which is caused by the lack of support from human resources both in quantity and quality, medical equipment and other supports both in type and number, and referrals that are not optimal, many residents complain of long queues in service, medicines are still limited then the procedure for patient service at the Puskesmas is slow. In addition, the existing facilities at the Curug Health Center are also inadequate. The focus of this study is more on what makes patient satisfaction at the Curug Health Center less good than services and facilities. The problems studied are social and dynamic problems, therefore, the researchers chose to use qualitative research methods to determine how to find, collect, process and analyze the data from the research. This qualitative research can be used to understand social interactions, for example by in-depth interviews with resource persons so that they will find clear information. The theory used in this research is to simplify service quality into five dimensions which are expressed by SERVQUAL Dimensions.